Using the Gensini score to estimate severity of STEMI, NSTEMI, unstable angina, and anginal syndrome. Issue 41 (15th October 2021) - Charach, Lior; Blatt, Alex; Jonas, Michael; Teodorovitz, Nick; Haberman, Dan; Gendelman, Gera; Grosskopf, Itamar; George, Jacob; Charach, Gideon
Abstract : Abstract: Gensini score (GS) provides valuable information on severity and prognosis of coronary artery disease (CAD). To evaluate the relationship between the severity of CAD determined by the GS and relation to ST-elevation myocardial infarction, non-ST segment elevation myocardial infarction (NSTEMI), unstable angina pectoris, chest pain (suspected angina syndrome on admission) and risk-factors for CAD and predictors of severity. Observational cross-sectional study. Consecutive patients who underwent clinically-indicated coronary angiography for ST-elevation myocardial infarction, NSTEMI, unstable angina pectoris or chest pain were enrolled. Among 600 patients, 417 (average age 67.8 ± 12.2 years) had CAD–related symptoms. Mean GS was 66.7 ± 63.8. Patients presenting with NSTEMI had the highest GS (81.3 ± 42.3; P < .001) Regression analysis of risk-factors showed the best association of GS with multivessel disease and coronary artery bypass graft. Regression analysis of medications showed that clopidogrel, had the best association with low GS. GS correlated with the severity of CAD, multivessel disease, coronary artery bypass graft, and troponin. GS was related to the cardiovascular risk-factors of diabetes, hypertension, and high-density cholesterol.